The Open Boat and the Shipwreck of the Singular: American Poetry and the Democratic Ideal - Elizabeth Willis (Transatlantica)
A poet investigates an essential contradiction within American poetry’s counter-tradition. How is it that vanguard works of poetry and prose repeatedly re-enact foundational narratives of Americanness ? What is the wager between being self-made and being part of ? How do scenes of self-determination and conquest play out generically and syntactically ? Throughout the 19th and 20th centuries, the trans-Atlantic movement of poetry, political theory, and property reiterates a tension between singularity and inclusion, political and linguistic representation. Works by Gertrude Stein, George Oppen, and Walt Whitman are considered in relation to the competing pressures of idiolectical invention and public address, of literary making and unmaking.